Covid-19 and social isolation: the mental health of higher education students - Oliveira, Eliany Nazaré (2023)
The objective was to analyze the relationship between the teaching-learning process and the mental health of higher education students in Ceará State, Brazil, during social isolation caused by the Covid-19 pandemic. An exploratory, descriptive, and cross-sectional study was conducted with 3,691 university students in 2020. The variables concerned with the continuity of the course in person, internet access conditions, and satisfaction regarding participation in pedagogical activities during isolation were analyzed. There were positive (r>0) and statistically significant (p<0.001) relationships between the MHI-38 Global Scale, the Positive well-being and Distress dimensions, the primary dimensions, and better internet access conditions and satisfaction with the pedagogical activities of the institution. On the other hand, negative (r<0) and statistically significant (p<0.001) relationships were found between the assessed dimensions and the concern with continuing the course in person. The primary dimensions tended to increase with increasing satisfaction with pedagogical activities and internet access conditions. On the other hand, the primary dimensions decreased with the increase in the concern with the continuity of the in-person course. The results suggest that the change in the teaching-learning model significantly impacted the students' mental health and that better conditions of access to activities tend to optimize the picture, while the intense scenario of concern makes the psychic illness more expressive. Therefore, it is up to the institutions to create and strengthen mental health policies for students.